Wetting Agent Influence on Water Infiltration into Hydrophobic Sand: II. Physical Properties. (1st September 2014) - Song, Enzhan; Schneider, Joseph G.; Anderson, Stephen H.; Goyne, Keith W.; Xiong, Xi
Abstract : Wetting agents are commonly used to remedy localized dry spot (LDS) caused by soil water repellency on golf course putting greens. Information gleaned from field experiments assessing wetting agent effects on infiltration can be difficult to interpret due to temporal and spatial variations. To avoid this challenge, a laboratory study was conducted to evaluate the influence of six commercial wetting agents at four concentrations (500, 1000, 3000, and 5000 mg L −1 ) on surfactant physical properties and to establish relationships between physical properties and water infiltration into a water‐repellent U.S. Golf Association (USGA)‐grade sand. As wetting agent concentration increased, notable decreases in surface tension (γ), liquid‐solid contact angle (θ), and liquid entry pressure head ( h p ) were measured. These decreases were negatively correlated with the hydraulic conductivity ( K ) of water‐repellent sands treated with wetting agents. Improved infiltration as a function of wetting agent concentration was explained by reduced hydrophobicity following wetting agent application. Cascade Plus and LescoFlo Ultra at concentrations of ≥3000 and 1000 mg L −1, respectively, transformed the water‐repellent sand to a wettable media, as evidenced by negative h p values. A multiple regression model ( R 2 = 0.82) found that K of wetting agent treated soil can be explicated by variables γ, h p, and wetting agent concentration. Our results showed that all tested wetting agents improved water infiltration, but the effectiveness was compound dependent. Therefore, it is essential to select appropriate wetting agents and application rates when seeking to improve water infiltration into hydrophobic sands.